Synthetic Studies on the Incorporation of N-Acetylallosamine in Hyaluronic Acid-Inspired Thiodisaccharides - Cristófalo, Alejandro Ezequiel (2021)
Two approaches for the synthesis of the thiodisaccharide β-S-GlcA(1→3)β-S-AllNAc are described here. The target disaccharide was a C-3 epimer and thio-analogue of the hyaluronic acid repetitive unit, tuned with a thiopropargyl anomeric group for further click conjugation. Thus, we analysed and tested two convenient sequences, combining the two key steps required to introduce the thioglycosidic bonds and consequently reach the target molecule: the SN2 substitution of a good leaving group (triflate) present at C-3 of a GlcNAc derivative and the introduction of the anomeric thiopropargyl substituent. The use of a 2-azido precursor showed to be a convenient substrate for the SN2 step. Nevertheless, further protecting group manipulation and the introduction of the thiopropargyl anomeric residue were then required. This approach showed to provide access to a variety of thiodisaccharide derivatives as interesting building blocks for the construction of neoglycoconjugates.